EFFORTS TO IMPROVE THE ECONOMIC LIFE OF THE BADUY COMMUNITY THROUGH THE AGRICULTURE SECTOR IN KANEKES VILLAGE, LEBAK DISTRICT BANTEN - Raden Irna Afriani; Listiawati Listiawati; Ahmad Mukhlis; Ihwan Satria Lesmana; Yuliah Yuliah; Surachman Surachman (International Journal of Engagement and Empowerment, 2022)
The Baduy people basically base their livelihoods on incipient agricultural production and hunting, and the dry land farming system with this type of agriculture only relies on lowland rice. Hunting is also only carried out in confined spaces in conventional forest areas. Wild species, deer, monkeys and honey. Until now the expertise of the Baduy community is still focused on the agricultural sector, hunting and starting to diversify plants, fruits and vegetables for household needs only. With such rapid population growth, which cannot be compared with traditional Baduy rural areas, the Baduy economy is experiencing tremendous pressure. Although the government's efforts above are aimed at finding a way out of all the limitations on the economic resources of the Baduy community, they have not succeeded in significantly increasing the welfare of the majority of the Baduy population. The Baduy community's economic system fully adheres to a market economy with currency as a medium of exchange. Since around 1970, the exchange system has been abandoned except for the limited needs of the clan environment. Although many Baduy people have moved and changed religions, their relationship as great-grandfathers is still well maintained. This real relationship is strengthened in the form of a more specific business relationship